Identification of rare paired box 3 variant in strabismus by whole exome sequencing - Hui-Min Gong; Jing Wang; Jing Xu; Zhan-Yu Zhou; Jing-Wen Li; Shu-Fang Chen (International Journal of Ophthalmology, 2017)
AIM: To identify the potentially pathogenic gene variants that contributes to the etiology of strabismus. METHODS: A Chinese pedigree with strabismus was collected and the exomes of two affected individuals were sequenced using the next-generation sequencing technology. The resulting variants from exome sequencing were filtered by subsequent bioinformatics methods and the candidate mutation was verified as heterozygous in the affected proposita and her mother by sanger sequencing. RESULTS: Whole exome sequencing and filtering identified a nonsynonymous mutation c.434G-T transition in paired box 3 (PAX3) in the two affected individuals, which were predicted to be deleterious by more than 4 bioinformatics programs. This altered amino acid residue was located in the conserved PAX domain of PAX3. This gene encodes a member of the PAX family of transcription factors, which play critical roles during fetal development. Mutations in PAX3 were associated with Waardenburg syndrome with strabismus. CONCLUSION: Our results report that the c.434G-T mutation (p.R145L) in PAX3 may contribute to strabismus, expanding our understanding of the causally relevant genes for this disorder.